Faktor Faktor yang Mempengaruhi Pemahaman UMKM dalam Penyusunan Laporan Keuangan Berdasarkan SAK ETAP (Studi Kasus pada Usaha Mikro Kecil Menengah di Kabupaten Jepara) - Yanto Yanto; Azis Ardi Prasetiyo (Jurnal Rekognisi Akuntansi, 2017)
One of the supporting factors that cause problems in developing Micro, Small and Medium Enterprises (MSMEs) is the lack of understanding of MSMEs in the preparation of financial reports based on SAK ETAP. This study aims to determine information and socialization, educational background, education level, length of business and business size on the understanding of MSMEs in preparing financial reports based on SAK ETAP. This research was conducted on micro, small and medium enterprises (MSMEs) furniture furniture in the District of Jepara. Research data were collected by distributing questionnaires to entrepreneurs and analyzed using multiple regression with the help of SPSS version 24. The results showed that information and socialization, educational background, education level, length of business, business size had a significant effect on the preparation of financial statements based on SAK ETAP.